Facile synthesis and application of multi-shelled SnO2 hollow spheres in lithium ion battery. Issue 63 (16th June 2016) - Wu, Guanglei; Wu, Hongjing; Wang, Kuikui; Zheng, Chenhui; Wang, Yiqun; Feng, Ailing
Abstract : A simple template-free hydrothermal method has been developed to prepare multi-shelled SnO2 hollow spheres with controlled interior texture. Abstract : A simple template-free hydrothermal method has been developed to prepare multi-shelled SnO2 hollow spheres with controlled interior texture. The interior texture and size of the multi-shelled SnO2 hollow spheres were found to be strongly dependent on the carbon source, Sn salt precursor and molar ratio of G : M. The multi-shelled SnO2 hollow spheres exhibit good electrochemical performance as the anode material in lithium ion batteries.